On the Origin of the 1,000 Hz Peak in the Spectrum of the Human Tympanic Electrical Noise - Pardo-Jadue, Javiera; Dragicevic, Constantino D.; Bowen, Macarena; Delano, Paul H. (Frontiers in Neuroscience, 2017)
The spectral analysis of the spontaneous activity recorded with an electrode positioned near the round window of the guinea pig cochlea shows a broad energy peak between 800 and 1000 Hz. This spontaneous electric activity is called round window noise or ensemble background activity. In guinea pigs, the proposed origin of this peak is the random sum of the extracellular field potentials generated by action potentials of auditory nerve neurons. In this study, we used a non-invasive method to record the tympanic electric noise (TEN) in humans by means of a tympanic wick electrode. We recorded a total of 24 volunteers, under silent conditions or in response to stimuli of different modalities, including auditory, vestibular, and motor activity. Our results show a reliable peak of spontaneous activity at ~1000 Hz in all studied subjects. In addition, we found stimulus-driven responses with broad-band noise that in most subjects produced an increase in the magnitude of the energy band around 1000 Hz (between 650 and 1200 Hz). Our results with the vestibular stimulation were not conclusive, as we found responses with all caloric stimuli, including 37ºC. No responses were observed with motor tasks, like eye movements or blinking. We demonstrate the feasibility of recording neural activity from the electric noise of the tympanic membrane with a non-invasive method. From our results, we suggest that the 1000 Hz component of the TEN has a mixed origin including peripheral and central auditory pathways. This research opens up the possibility of future clinical non-invasive techniques for the functional study of auditory and vestibular nerves in humans.